RESOLVING HUMAN-WILDLIFE CONFLICT: A CASE STUDY OF SOCIO-ECONOMIC IMPACTS AND MITIGATION STRATEGIES IN PERUVANTHANAM GRAMA PANCHAYAT - James, Jaimol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Crop destruction caused by wild animals constitutes a significant global challenge, profoundly impacting agricultural communities with far-reaching economic and livelihood consequences. This investigation centres on Peruvanthanam Panchayat in Kerala's Idukki district, a region where wildlife exerts substantial pressure on farmers by severely compromising crop yields. The study meticulously evaluates the extent of crop damage, appraises existing mitigation strategies, and assesses their efficacy. Applying inferential statistics, regression analysis, and sophisticated modelling techniques delves into the socio-economic and ecological drivers of crop depredation. The ultimate goal is to craft actionable, evidence-based recommendations to support local farmers. The findings are essential for achieving a delicate equilibrium between agricultural productivity and wildlife conservation.